1999
DOI: 10.3109/10428199909145951
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coagulation Disorders in Patients with Acute Leukemia Before and After Cytostatic Treatment

Abstract: Coagulation disorders are often the reason for fatal bleeding in acute promyelocytic leukemia. Their occurrence as well as pathogenesis and prognostic significance in other subtypes of acute myelogenous leukemia and acute lymphoblastic leukemia is less known. Tests were carried out in 70 patients including 49 with AML and 21 with ALL. In all patients thrombin-antithrombin complexes (TAT), D-dimer (DD) and plasmin-antiplasmin complexes (PAP), antithrombin III activity, fibrinogen/fibrin degradation products, AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 14 publications
4
21
0
1
Order By: Relevance
“…According to the JMHW criteria, 45% of non-APL AML patients developed DIC during induction therapy, which was consistent with previous findings [3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to the JMHW criteria, 45% of non-APL AML patients developed DIC during induction therapy, which was consistent with previous findings [3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 89%
“…DIC has often been associated with bleeding manifestations in AML cases, especially in APL cases [3][4][5][6][7][8]. DIC also occurs as a devastating complication in patients with other types of AML.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Coagulation disorders are already present in the majority of patients with AL at the time of diagnosis [1]. Most commonly they appear in laboratory tests and correspond with chronic activation of the coagulation system, manifested in the elevation of such activation markers as F1 þ 2, TAT, DD and PAP [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation disorders can also occur in other acute myelogenous leukemia (AML) subtypes and in patients with acute lymphoblastic leukemia (ALL). In our previous study we have showed that in the majority of patients with acute leukemia (AL) changes indicating chronic activation of coagulation system are already present at the time of diagnosis [1]. Additionally, these changes can be enhanced by chemotherapy.…”
Section: Introductionmentioning
confidence: 97%